Sosok Perempuan Dalam Puisi “Asyhadu An Lâ Imra’ata Illâ Anti” Karya Nizar Qabbani - Dewi Lutfiana Hayati; Daris Syafaah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
Abstract Poetry research with the title "I witness that there is no woman Apart From You" by Nizar Qabbani. Poetry has beautiful words that describe social conditions even to the point of economic and political. The purpose of this study was to find out the meaning contained in the poem "I witness There Is No Woman Besides You and to know the aspects of the signified and the aspect of the signifier. The form of the formulation of the problem contained in this poem are: 1) What are the characteristics of women in the poem "I bear witness that there is no woman but you"? 2) How does the female figure compare the poet to the poem?. The method used in this study uses qualitative methods. And this research was studied using semiotic analysis. Semiotics is the study of signs and meanings contained in literary works. The findings of this study are that there are aspects of signifier and signified . the characteristics of women described in the verses of the poem "I witness there is no woman but you". While the results of the research in this poem explain the figure of a woman, namely the most loved wife, who is able to nurture and care for her patiently which is like taking care of her young child, tough, affectionate, patient and able to accompany the poet in times of joy and sorrow. Keywords: Poetry, I Witness There Is No Woman Apart From You, Semiotics Asbtrak Penelitian puisi dengan judul “ Asyhadu An La> Imra’ ata Illa< Anti ” karya Nizar Qabbani. Puisi memiliki kata-kata yang indah yang menggambarkan keadaan sosial bahkan sampai ekonomi dan politik. Tujuan penelitian ini untuk mengetahui makna yang terkandung dalam puisi “Aku Bersaksi Tiada Perempuan Selain Engkau, dan mengetahui aspek petanda dan paspek penanda. Bentuk rumusan masalah yang terdapat dalam puisi ini yaitu: 1) Bagaimana sifat-sifat wanita yang terdapat dalam puisi “Aku Bersaksi Tiada Perempuan Selain Engkau”? 2) Bagaimana sosok wanita tersebut mengumpamakan sang penyair pada puisi tersebut?. Adapun metode yang digunakan dalam penelitian ini menggunakan metode kualitatif. Dan penelitian ini dikaji menggunakan analisis semiotika. Semiotika adalah ilmu yang mengkaji tentang tanda dan makna yang terdapat dalam karya sastra. Adapun temuan dari penelitian ini yaitu terdapat aspek petanda dan penanda, sifat-sifat wanita yang dijelaskan pada bait-bait puisi “Aku Bersaksi Tiada Perempuan Selain Engkau”. Sedangkan hasil penelitian dalam puisi ini menjelaskan sosok wanita yaitu istri yang paling dicintai, yang mampu mengayomi serta merawat dengan telaten yang diibaratkan seperti merawat anaknya yang masih kecil, tangguh, kasih sayang, penyabar dan mampu mendampingi sang penyair dalam keadaan suka maupun duka. Kata Kunci: Puisi, Aku Bersaksi Tiada Perempuan Selain Engkau, Semiotika